Growth of GaN@InGaN Core-Shell and Au-GaN Hybrid Nanostructures for Energy Applications - Tevye Kuykendall; Shaul Aloni; Ilan Jen-La Plante; Taleb Mokari (International Journal of Photoenergy)
We demonstrated a method to control the bandgap energy of GaN nanowires by forming GaN@InGaN core-shell hybrid structures using metal organic chemical vapor deposition (MOCVD). Furthermore, we show the growth of Au nanoparticles on the surface of GaN nanowires in solution at room temperature. The work shown here is a first step toward engineering properties that are crucial for the rational design and synthesis of a new class of photocatalytic materials. The hybrid structures were characterized by various techniques, including photoluminescence (PL), energy dispersive x-ray spectroscopy (EDS), transmission and scanning electron microscopy (TEM and SEM), and x-ray diffraction (XRD).